Recent advances and new species in aquaculture - Fotedar, Ravi K.; Phillips, Bruce F. (Chichester, UK : Wiley-Blackwell Pub., 2011)
This comprehensive, up-to-date text delivers the latest must-have information on species new to aquaculture and documents the most important technological innovations of the past decade. Every aspect of the growing field has been addressed with coverage spanning recent technological development, new species, recent changes and global trends. More specifically, you will find information on the culture of species such as barramundi, cobia, dolphin fish, spiny lobsters, slipper lobsters, mud crabs, penaeid prawns, Nile tilapia, yellow king fish, abalone, sea cucumber and sea urchin, seaweed, ornamentals and Indian major carps, fugu, mud skippers, cephalopods and blue fin tuna. The technological innovations and introduction of new species into aquaculture are critical to the evolution of the global aquaculture industry; an industry which is rapidly becoming one of the fastest growing in the world, having experienced huge advances across its many and diverse facets. Recent Advances and New Species in Aquaculture focuses explicitly on the ever-changing face of aquaculture, providing core scientific and commercially useful information on the remarkable growth in aquaculture production and in the advancement of new technological tools. Written by many well respected international figures and drawn together and edited by Ravi Fotedar & Bruce Phillips, this exciting book is an essential purchase for anyone involved in or about to enter into the aquaculture industry. Libraries in all universities and research establishments where aquaculture, fish biology, aquatic and environmental sciences and fisheries are studied and taught will find this an important addition to their shelves. Recent Advances and New Species in Aquaculture is sure to become a key companion for all those studying aquaculture and a valuable source of reference for all personnel involved in the industry.
A global review of spiny lobster aquaculture -- Slipper lobsters -- Mud crab aquaculture -- Penaeid prawns -- Cobia culture -- Barramundi aquaculture -- Abalone culture -- Seaweed aquaculture, utilisation, and a review of cultivation in Latin America -- Marine ornamental fish culture -- Tilapia -- Carp polyculture in India -- Future directions.
Includes bibliographical references and index.
Print version record.
Keywords: Aquaculture; Aquaculture -- methods; Fishes; Palinuridae; TECHNOLOGY & ENGINEERING -- Agriculture -- General; Aquaculture; Electronic books; Electronic resource